Iron(iii)-catalyzed aerobic dioxygenation of styrenes using N-hydroxyphthalimide and N-hydroxybenzotriazole. Issue 12 (29th February 2016) - Bag, Raghunath; Sar, Dinabandhu; Punniyamurthy, Tharmalingam
Abstract : The dioxygenation of alkenes with NHPI/HOBt in air is described using commercial iron salt as the catalyst under ambient conditions with a broad substrate scope and functional group tolerance. The products can be readily converted into the corresponding 1, 2-diols in high yields. Abstract : Iron-catalyzed dioxygenation of alkenes in air using N -hydroxyphthalimide (NHPI) and N -hydroxybenzotriazole (HOBt) is described at room temperature. The products can be readily converted into 1, 2-vicinal diols using PPh3 and Mo(CO)6 . The use of Fe(NO3 )3 ·9H2 O as the catalyst, mild reaction conditions and the selectivity are the significant practical features. The radical scavenger experiment suggests that the reaction proceeds via a radical intermediate. The synthetic and mechanistic aspects have been presented.